Analisa Manajemen Resiko Untuk Mengurangi Moral Hazard Nasabah Pembiayaan Murabahah BRI Syariah Pare - M. Soleh Mauludin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
This study aims to analyze the extent to which risk management is carried out by Islamic banks in minimizing losses due to moral hazard committed by murabahah financing customers. Research that uses a qualitative approach, agency theory, and research objects at BRI Syariah Pare in 2019 resulted in findings that BRI Syariah uses the 5C analysis process, namely character, capacity, capital, collateral ), and conditions (conditions) in order to minimize moral hazard for murabahah financing customers.